Detection of Thiopurine S-Methyltransferase (TPMT) Polymorphisms TPMT*3A, TPMT*3B and TPMT*3C in Children with Acute Lymphoblastic Leukemia - Nawar S. Mohammed; Manal K. Rasheed; Hasanein H. Ghali; Shaymaa J. Ahmed (مجلة كلية الطب, 2018)
Background: Thiopurines are essential medications in Acute Lymphoblastic Leukemia (ALL) treatment protocols as anti-cancer agents since long time; however, their use might result in unexpected toxicities in ALL children due to the low thiopurine S-methyltransferase (TPMT) activity, a major enzyme involved in 6- mercaptopurine metabolism, which strongly correlates to the genetic polymorphism of the TPMT gene in those patients.